Between universalism and targeting: Exploring policy pathways for an Australian Basic Income. (December 2020) - Spies-Butcher, Ben; Phillips, Ben; Henderson, Troy
Despite growing interest in proposals for a universal basic income, little advance has been made in implementation. Here we explore policy options for an Australian Basic Income. Our analysis responds to concerns that Basic Income is both too expensive and too radical a departure from existing welfare state structures to be a feasible policy option. Drawing on policy and Basic Income scholarship we identify changes to Australia's current means-tested benefits structures that move substantially towards Basic Income while remaining consistent with historic policy norms, which we call 'affluence testing'. Using microsimulation we explore fiscal and distributional trade-offs associated with the implementation of an affluence-tested Basic Income. Our results suggest Basic Income has the potential to significantly reduce inequality and poverty while also requiring taxes to rise substantially. Placing these trade-offs in international context we find the policy would reduce inequality to levels similar to Nordic welfare states while increasing overall taxation to approximately the OECD average. JEL Codes: I3, H2, H5